“Diagnóstico, incidencia y severidad de enfermedades fungosas en ecotipos regionales de Phaseolus Vulgaris l. en el fundo Aucaloma de la UNSM – T” - Yrigoín Pérez, Amilton (2017)
This research was conducted at the farm "Aucaloma" from the National University of San Martín - T, Morales District located in the province of San Martin, San Martin department, with a geographical location of 76 ° 27 '55 "W, 6 ° 29 '40 "south latitude and 295 msnmm, with the aim of" Diagnose and assess the incidence and severity of fungal diseases in Phaseolus vulgaris regional ecotypes "; for which I had to isolate, purify and characterize fungi causing diseases in beans ecotypes regional study (Huasca beans, Pajatino, Allpa, Awisho, yellow Panamito T.), likewise the incidence and severity of assessed fungal diseases in each ecotype, and grain yield (kg / ha) were determined. The following diseases, fungal damping, wilting, web blight, angular spots, angular leaf spot gray, lunar spot were identified and anthracnose caused by the fungus Fusarium solani, Sclerotium rolfsii, Rhizoctonia solani, Cercospora canescens, Pseudocercosporella albida, Curvularia lunata and Colletotrichum lindemutianum; well none of the beans ecotypes study show reaction to identified disease susceptibility; however Pajatino and Awisho were those with higher level of resistance (as multivariate analysis); reaching yields of 1268 and 919 kg / ha; associated fungal pathogens were also identified other: Nigrospora sphaerica, Botrytis sp, Colletotrichum lindemuthianum and Cercospora vanderysti associated, Cercospora canescens, and Cercospora canescens, respectively. The highest grain yield under the conditions of study, obtained Huasca bean ecotype with an average of 1411 kg / ha. Keywords: bean common, diagnosis, incidence, severity, ecotypes, pathogenic fungi.